Introduction to Solid Mechanics - Shames I. H. Irving (New Delhi, Prentice Hall of India Private Limited, 2002)
This introduction to solid mechanics provides a clear, rigorous treatment of the principles underlying practices so-that students know the theory well enough to solve problems from first principles. A wealth of examples illustrate the meaning of the theory without simply offering recipes or maps for soMncLsimilar problems. Generous explanations are made in examples to elaborate how the theory and modeling have been applied. In short, examples are meant more to be read and studied and less to be mapped To familiarize students with the use of modern engineering computer-based tools, several end-of-chapter problems are specially design oriented to help foster computer programming skills. Finally, the book introduces_the finite element method so that students understand the when they use finite element codes for computing stresses in their design projects.